Chain extension in poly(butylene-adipate-terephthalate). Inline testing in a laboratory internal mixer. (April 2015) - Costa, Anna Raffaela M.; Almeida, Tatiara G.; Silva, Suédina M.L.; Carvalho, Laura H.; Canedo, Eduardo L.
Abstract: This contribution is concerned with degradation and chain extension in poly(butylene-adipate-terephthalate), PBAT, compounded in a laboratory internal mixer with an epoxydic chain extender additive. Weight-average mass change during melt processing was estimated from temperature-torque-time data recorded by the equipment. The effect of the additive was found to be strongly dependent on processing temperature, and weakly dependent on concentration. Molar mass more than doubled at 230°C with 2% additive. Long induction times and catastrophic failure to mix, occasionally observed with oligomeric additives processed in internal mixers, are discussed. Possible implementation of the procedure for real-time estimate of chain extension is also discussed.